Perfused Gills Reveal Fundamental Principles of pH Regulation and Ammonia Homeostasis in the Cephalopod Octopus vulgaris - Hu, Marian Y.; Sung, Po-Hsuan; Guh, Ying-Jey; Lee, Jay-Ron; Hwang, Pung-Pung; Weihrauch, Dirk; Tseng, Yung-Che (Frontiers in Physiology, 2017)
In contrast to terrestrial animals most aquatic species can be characterized by relatively higher blood NH4+ concentrations despite its potential toxicity to the central nervous system. Although many aquatic species excrete NH4+ via specialized epithelia little information is available regarding the mechanistic basis for NH3/NH4+ homeostasis in molluscs. Using perfused gills of Octopus vulgaris we studied acid-base regulation and ammonia excretion pathways in this cephalopod species. The octopus gill is capable of regulating ammonia (NH3/NH4+) homeostasis by the accumulation of ammonia at low blood levels (< 260 µM) and secretion at blood ammonia concentrations exceeding in vivo levels of 300 µM. NH4+ transport is sensitive to the adenylyl cyclase inhibitor KH7 indicating that this process is mediated through cAMP-dependent pathways. The perfused octopus gill has substantial pH regulatory abilities during an acidosis, accompanied by an increased secretion of NH4+. Immunohistochemical and qPCR analyses revealed tissue specific expression and localization of Na+/K+-ATPase, V-type H+-ATPase, Na+/H+-exchanger 3 and Rhesus protein in the gill. Using the octopus gill as a molluscan model, our results highlight the coupling of acid-base regulation and nitrogen excretion, which may represent a conserved pH regulatory mechanism across many marine taxa.